Fitorremediação: uma técnica potencial em áreas agrícolas contaminadas com metais pesados - Nogueira, Samuel Baldin (Universidade Federal de São Carlos, 2022)
Soil contamination, caused by rapid human development, negatively affects the quality and quantity of food. Among the contaminants, heavy metals (HMs) are notorious because they cause harmful effects on humans, such as DNA deterioration and inhibition of neurotransmitters. In addition, HMs negatively affect plant organisms, causing a decrease in photosynthetic and plant growth, etc. Currently, Brazil is listed among the countries in the ecological risk zone due to HMs; furthermore, it has records of contamination by these elements in agricultural areas in the São Paulo state. Thus, it is essential to use techniques that decontaminate soils, and among these techniques, there is phytoremediation. This technique uses plantsas remedial agents so that the plant organisms will remediate the contaminants. Plant species suitable for these functions need to have specific "skills", such as the hyperaccumulation of contaminants and tolerance to abiotic stresses, for example, turnip (Brassica rapa L.). Phytoremediation is indicated as sustainable and economically viable; however, no studies in Brazil indicate and prove its economic viability, making it a "gap" in the national literature. Therefore, to solve this scarce information, we conducted a hypothetical scenario of a sugarcane field in Mogi Guaçu-SP, which presented contamination above the limit allowed by CETESB (cetesb.sp.gov.br/areas-contaminadas/relacao-de-area-contaminadas) for pollutants categorized by 'metals' (generic definition established by this state agency), so we simulated the performance of agricultural land remediation using turnip as a phytoremediator. We use microeconomics concepts to perform financial calculations and conduct questionnaires with producers, resellers, and bioenergy plants to estimate production price. Our results were published in the journal 'Revista Ciência, Tecnologia e Ambiente' in a 'Research Article format' in 2022 [doi.org/10.4322/2359-6643.12213]. We found that the economic deficit caused by phytoremediation was US$ 536.43/ha, which is higher than the annual profit from sugarcane production, US$178,81/ha. Furthermore, in our hypothetical scenario, the cost of phytoremediation in m³ (considering 0.20m depth) is ~US$5. Therefore, we conclude that phytoremediation is a potential and easily applicable technique for the decontamination and conservation of soils polluted with HMs in Brazilian agricultural lands.
Phytoremediation: potential technique in arable lands contaminated with heavy metals
Keywords: Brassica rapa; Fitorremediação; Metais pesados; Viabilidade econômica; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA